The (Im)Possibility of Religious Reasoning in the Formal Public Sphere - Kalkauskaitė, Vaida (Religija ir kultūra, 2015)
[full article and abstract in Lithuanian; abstract in English]This article focuses on the debate between Jürgen Habermas and Charles Taylor on the place of religious argumentation in the formal public sphere. Habermas’s position, which arises from his critique of John Rawls’s position and is also its continuation, is based on the principle of common reason. In order to use their arguments in the public sphere, religious people must translate them into secular language, which is supposedly understood by every rational person. Taylor opposes this position by stating that the division between religious and secular arguments is not well enough reasoned. The aim of this article is to find out whether the views of Hebarmas, as well as the core presuppositions that they are based on, can stand their ground and whether they are capable of reflecting the current geopolitical and sociocultural situation and help in understanding it. This is done by using the points made by Taylor and other authors who support his views and trying to find a satisfactory alternative solution.
Keywords: Charles Taylor; Jürgen Habermas; formal public sphere; religion